The Emulsion Stability, Antioxidant and Color L, a, b Content on Reduced Fat Mayonnaise Using Virgin Coconut Oil - Citravia Agustin; Ilvan Dian Kusuma; Imam Thohari (Faculty of Animal Science Universitas Brawijaya, 2023)
Mayonnaise is the most favorite product that made from yolk and vegetable oil so it contain of 70-80% fat. The risk of high fat intake is deteriorating health so the percentage oil on mayonnaise have to decrease as reduced fat mayonnaise (RFM). Virgin Coconut Oil (VCO) is one of the various type vegetable oil that can used to make mayonnaise, and there have been several reports describing health benefit. This study was to determine the best percentage of the VCO based on emulsion stability, antioxidant and color L,a,b. The method used experimental laboratory and Completely Randomized Design (CRD) with fourth treatments and fourth replication. It consisted using VCO 70%, 60%, 50% and 40%. The result of this research gave significantly effect (P<0.01) on emulsion of stability, antioxidant and color test. The conclusion of this research was best formulation of RFM using VCO based emulsion stability, antioxidant and color test is 60% it was 80.50±0.57; and 20.65±0.55.